Graphite-type activated carbon from coconut shell: a natural source for eco-friendly non-volatile storage devices. Issue 5 (13th January 2021) - Keppetipola, Nilanka M.; Dissanayake, Maithri; Dissanayake, Pubudu; Karunarathne, Buddhika; Dourges, Marie Anne; Talaga, David; Servant, Laurent; Olivier, Céline; Toupance, Thierry; Uchida, Satoshi; Tennakone, Kirthi; Kumara, G. R. Asoka; et al.
Abstract : Simple ecofriendly activation process of carbon obtained from coconut shell-based waste was used for the fabrication of non-volatile high performance supercapacitors. Abstract : Carbon from biomass as an active material for supercapacitor electrodes has attracted much interest due to its environmental soundness, abundance, and porous nature. In this context, activated carbon prepared from coconut shells via a simple activation process (water or steam as activation agents) was used as an active material in electrodes for eco-friendly supercapacitors. X-ray diffraction (XRD), Raman spectroscopy, conductivity, scanning electron microscopy (SEM), N2 sorption and thermogravimetry coupled to mass spectrometry (TGA-MS) studies revealed that activated carbon produced by this approach exhibit a graphitic phase, a high surface area, and large pore volume. The energy storage properties of activated carbon electrodes correlate with the morphological and structural properties of the precursor material. In particular, electrodes made of activated carbon exhibiting the largest Brunauer–Emmett–Teller (BET) surface area, i.e. 1998 m 2 g −1, showed specific capacitance of 132.3 F g −1 in aqueous electrolyte (1.5 M H2 SO4 ), using expanded graphite sheets as current collector substrates. Remarkably, this sample in a configuration with ionic liquid (1-methyl-1-propy-pyrrolizinium bis(fluorosulfonyl)mide) (MPPyFSI) as electrolyte and a polyethylene separator displayed an outstanding storage capability and energy-power handling capability of 219.4 F g −1 with a specific energy of 92.1 W h kg −1 and power density of 2046.9 W kg −1 at 1 A g −1 and maintains ultra-high values at 30 A g −1 indicating the ability for a broad potential of energy and power related applications. To the best of our knowledge, these values are the highest ever reported for ionic liquid-based supercapacitors with activated carbon obtained from the biomass of coconut shells.